Hubungan Antara Self Compassion Dengan Work Family Conflict Pada Staf Markas Palang Merah Indonesia Provinsi Jawa Tengah - Hidayati, Frieda N.R (Faculty of Psychology, Diponegoro University, 2015)
Staff of Red Cross Headquarters, in carrying out their duties in accordance with the mission of the organization engaged in humanitarian, are expected to always be sensitive, responsive and fast moving. The demands of work often have to deal with the demands of the role within the family, referred to as experiencing work-family conflict. This study aimed to measure the correlation between self – compassion to work family conflict on staff of Red Cross Indonesia Headquarters of Central Java. Research subjects consisted of 196 permanent employees of Red Cross Indonesia headquarters in Central Java. Results from this study showed that the hypothesis stated, there is a negative relationship between self-compassion and work family conflict, was accepted (r = -.438, p< .001) The higher self – compassion, the lower the work family conflict.